Effect of iron injection strategies for suckling piglets on pre- and post-weaning growth performance and hematocrit levels - Lima, Gabriella; Lemanski, Clara M; Rank, Ana N; Jang, Young-Dal (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: A single, 200-mg iron injection for newborn pigs is a common practice in swine production. It is required to provide sufficient iron for newborn pigs while avoiding the potential risk of excessive amount of iron causing oxidative stress. Objective: To evaluate the quantity and timing of a single or second iron injection into suckling piglets on growth performance and hematocrit levels. Methods: A total of 24 piglets from four litters were used in each experiment (3). Treatments were: Experiment 1- 1) Control: 150 mg iron injection at d 1-3 of age, 2) Iron14: additional 100 mg iron injection at 14 d before weaning, and 3) Iron7: additional 100 mg iron injection at 7 d before weaning; Experiment 2- 1) Control: 100 mg iron injection at d 1-3 of age, 2) Iron100/100: 100 mg iron at d 1-3 of age and 9 d after the first injection, and 3) Iron200: 200 mg iron injection at d 1-3 of age; and Experiment 3 (at d 3-4 of age)- 1) Fe100: 100 mg iron injection, 2) Fe200: 200 mg iron injection, and 3) BW200: 125 mg iron injection/kg body weight. Pigs were weaned at d 25-28 of age. Growth performance and hematocrit levels were measured until d 13-14 postweaning. Results: In Experiment 1, the Iron14 treatment had a greater final body weight than the control treatment (p=0.07). Hematocrit levels were greater in the Iron14 (p=0.10) and Iron7 (p<0.05) treatments than in the control treatment at d 14 postweaning. In Experiment 2, average daily gain in the postweaning period was greater in the Iron100/100 treatment than in the control (p<0.05) and Iron200 (p=0.08) treatments. Hematocrit levels in the Iron200 treatment were greater than those in the control treatment (p<0.05) at d 13 postweaning. In Experiment 3, there was no difference in growth performance, but the BW200 treatment increased hematocrit levels to a greater degree than the Fe200 treatment (p<0.10). Conclusion: An additional iron injection earlier and a split iron injection to newborn pigs could benefit postweaning growth, but not by body weight-based iron injection. Hematocrit levels increase with a greater dose of iron injected although the magnitude varies depending on injection strategies.